Long-Term Suppression of Hardwood Regeneration by Chinese Privet (Ligustrum sinense) - Turner, Taylor N.; Dean, Thomas J.; Kuehny, Jeff S. (Frontiers in Forests and Global Change, 2022)
Native hardwood regeneration in the southeast United States is hindered by repeat disturbance events and the presence of invasive species. Our study aimed to determine the ability of native species in an unmanaged urban forest fragment to persist following high winds from hurricane Gustav in 2008 and subsequent salvage logging. In 2009, researchers estimated the density and composition of the regeneration and overstory trees as well as percent crown cover of invasive Chinese privet. Percent Chinese privet cover was visibly high, leading them to believe it may be inhibiting native hardwood establishment. Ten years later in 2019, we returned to the plots to take repeat measurements. Forest composition remains the same and privet crown cover remains high. There has been no increase in regenerating individuals and overstory trees per hectare and basal area remains low. These results confirm that the heavy Chinese privet presence is persistent long term and will require management to promote reproduction of native overstory tree species.